The use of newly isolated fungal cultures for the selective delignification of bamboo culms - Zhao, Bo; Liu, Rui; Guo, Qi; Xu, Gang; Zhang, Li; Sun, Peng; Cao, Ying; Hu, Shanglian (Frontiers in Bioengineering and Biotechnology, 2023)
The screening of ligninolytic enzyme-producing fungal species in samples led to the identification of Paracremonium sp. LCB1, Clonostachys compactiuscula LCD1 and Clonostachys compactiuscula LCN1. Both these strains produced high levels of hemicellulase and ligninolytic enzyme production over a relatively short fermentation period of 3-5 days while exhibiting very low levels of cellulase activity. The results of the tests indicated that co-culturing LCB1 and LCN1 enhanced the ability to degrade lignin, and the ideal degrading circumstances and internal degrading mechanism of combined fungi were examined. The results showed that under conditions of temperature (30 °C), pH (5), culture time (40 d), solid-liquid ratio (1:2.5), the pretreatment of bamboo culms with a co-culture of LCB1 and LCN1 resulted in a pronounced 76.37% drop in lignin weight and a high lignin/cellulose loss ratio (>10).Fourier transform infrared spectroscopy, X-ray diffractometry, and scanning electron microscopy were used to characterize the physicochemical properties of these biopretreated bamboo culms, further confirming that LCB1 and LCN1 co-culture represents an effective approach to bamboo delignification.